The Colour Card Game - Peacock-Smith, R.; Green-Armytage, Paul (The Colour Society of Australia, Inc., 2009)
This paper is the outcome of a dialogue between two lecturers in the visual arts from universities in Queensland and Western Australia. The Colour Card Game is a tool for teaching creative colour exploration to a wide variety of students from different educational disciplines and from different cultural backgrounds. The aim is to engage students in a way that is not intimidating, requires no special skills or preparation, and with any value judgments coming from the students rather than from the teacher. The game is played with the commercial paint sample cards that are freely available from paint and hardware stores. The object of the game is to produce unusual colour combinations that ‘work’ (are considered creatively harmonious). There is an element of chance in the distribution of colour cards and opportunities for players to exchange cards that they find unworkable. At the conclusion of play the colour combinations are displayed and players vote for the ones they consider most successful. The game provides the opportunity to discuss different approaches to colour combination: reliance on one’s own judgment, application of established theories of colour harmony, making use of the findings of research and using chance processes to open up a wider range of possibilities. Students learn to look at colours with fresh eyes and to escape from personal limitations, prejudices, rules and the dictates of fashion. They explore unfamiliar areas of colour space and discover how colours actually interact. The game has been played successfully in the classroom and in social situations. Players enjoy the game; they find it challenging, stimulating and often revealing of personal tastes in colour. The paper describes the game’s development, purposes and applications within teaching context, variation of play and possible future developments.